Sistem Pendukung Keputusan Untuk Penentuan Calon Ketua Federasi Olahraga Karate-Do Indonesia(Forki)Toba Samosir Dengan Metode Weighted Product(WP) - Hutagaol, Roy Agung; Nadeak, Berto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Decision Support System (DSS) as a computer-based system that helps in the process of making an adaptive, interactive, flexible decision, which is specifically developed to support the solution of unstructured management problems. to improve the quality of decision making. One of them is for the selection of candidates for chairman of the Karate-Do Indonesia Sports Federation (FORKI) Toba Samosir, which so far the selection process has been carried out by means of voting between the implementing committee only so that the assessment is less objective. So to solve this problem this study uses the Weighted Product (WP) method for the selection of candidates for chairman of the Indonesian Karate-Do Sports Federation (FORKI) Toba Samosir and helps the decision-making process. The criteria used for selection are Understanding Management, Integrity, Leadership, Achievement, Belt Rankings. With the results of the Decision Support System for the Selection of Candidates for the Chair of the Indonesian Karate-Do Sports Federation (FORKI) Toba Samosir can assist in conducting assessments according to predetermined criteria. After being processed using an application that applies the WP method, the best candidate is recommended to be the candidate for chairman of the Indonesian Karate-Do Sports Federation (FORKI) Toba Samosir, so that the assessment is more objective